Azerbaijani educators about the role of women in society and the education of women in the II half of the XIX century - Вaгaбовa Т. А. (Journal of Oriental Studies, 2018)
The article analyzes the struggle of Azerbaijani educators at the beginning of XX century for women’s rights and education. In the work of Azerbaijani educators as M.F. Akhundov, Zardabi, M. Shahtahtly, N. Vezirov, M.T. Sidgi, F. Kocharli who lived at the beginning of the XX century, there are interesting thoughts about women’s education and upbringing. As a result of their struggle for the first time in the East World School opened in Azerbaijan, recognized the right of women to choose and elect.